PENGARUH INTEGRASI NILAI-NILAI IMTAQ PADA MATERI STRUKTUR ATOM TERHADAP MOTIVASI DAN KARAKTER RELIGIUS - Nurhusnul Khatimah; Khaeruman Khaeruman; Yusran Khery (IKIP Mataram, 2014)
Lack of awareness of: courtesy, dishonesty while performing individual tasks, being dishonest in daily tests, and not being obedient to the teacher's instructions is due to the lack of Imtaq process. To solve it is by integrating Imtaq values with learning materials. This study aims to determine the effect of integration of Imtaq values on the material of atomic structure to motivation and religious character. The research was conducted in class X MAN 1 Mataram during August until September 2014. The subjects of the study were students of class X IPA-2 (as experiment) and X IPS-3 (as control) were 37 and 39 students respectively. This research is a quasi- experiment with posttest-control group design. Data of research result are motivation and religious character. The instrument of data collection is a questionnaire of motivation and questionnaire of religious character which has been tested its validity and reliability on 76 subjects who have the same characteristics of age and level of education with the subject of research. The data were analyzed using normality test followed by kolmogorov-smirnov test. The results showed that there is an effect of integration of imtaq values on the material of atomic structure to motivation and religious character.